Prevalence of gastrointestinal parasites in dairy cows of family-type production system - Ortiz-Muñoz, Iris Yaratzmín; Salinas-Rios, Teodulo; Pérez-León, María Isabel; Aquino-Cleto, Magaly; Rodríguez-Magadán, Héctor Maximino; Hernández-Bautista, Jorge (Ecosistemas y Recursos Agropecuarios, 2022)
Endoparasites is a common problem affecting mainly dairy herds health and productivity. The objective was to determinate the body condition, number of births, and time of year effect on gastrointestinal parasites presence in family dairy cows established in District of Etla and Zimatlán de Álvarez, Oaxaca, México. The study was carried out in spring, summer, autumn and winter, using 185 Holstein cows (116 from Etla and 69 from Zimatlán de Alvarez), with different body condition (≤ 2.0, 2.5 and ≥3) and Number of Births (1-3 and 4-6). Fecal samples were analyzed using flotation technique with saturated sodium chloride solution. Data were analyzed with a variance analysis through a categorical data model (p < 0.05), considering as fixed effects body condition, number of births, time of year and districts. 62.48% of cows had endoparasites, with no difference between districts. Eimeria spp. was higher (p < 0.05) in both Districts. Cryptosporidium, Strongyloide and Oesophagostomum were higher (p < 0.05) in Zimatlán de Álvarez. The number of cases increased (p < 0.05) in spring and summer. It is concluded that climatic conditions, body condition and number of births contribute to increased gastrointestinal parasites, mainly Eimeria spp., in family dairy cows in the Districts of Etla and Zimatlán of Alvarez.